Anoectochilus roxburghii Extract Extends the Lifespan of Caenorhabditis elegans through Activating the daf-16/FoxO Pathway - Peng Xu; Jianfeng Wang; Junyi Wang; Xiaoxiao Hu; Wei Wang; Shengmin Lu; Yingkun Sheng (MDPI AG, 2024)
As a significant global issue, aging is prompting people's interest in the potential anti-aging properties of Anoectochilus roxburghii (A. roxburghii), a plant traditionally utilized in various Asian countries for its purported benefits in treating diabetes and combating aging. However, the specific anti-aging components and mechanisms of A. roxburghii remain unclear. This study aims to investigate the anti-aging effects and mechanisms of A. roxburghii extract E (ARE). Caenorhabditis elegans (C. elegans) were exposed to media containing different concentrations of ARE whose superior in vitro radical scavenging capacity was thus identified. Lifespan assays, stress resistance tests, and RT-qPCR analyses were conducted to evaluate anti-aging efficacy, reactive oxygen species (ROS) levels, antioxidant enzyme activity, and daf-16, sod-3, and gst-4 levels. Additionally, transcriptomic and metabolomic analyses were performed to elucidate the potential anti-aging mechanisms of ARE. Fluorescence protein assays and gene knockout experiments were employed to validate the impacts of ARE on anti-aging mechanisms. Our results revealed that ARE not only prolonged the lifespan of C. elegans but also mitigated ROS and lipofuscin accumulation, and boosted resistance to UV and heat stress. Furthermore, ARE modulated the expression of pivotal anti-aging genes including daf-16, sod-3, and gst-4, facilitating the nuclear translocation of DAF-16. Significantly, ARE failed to extend the lifespan of daf-16-deficient C. elegans (CF1038), indicating its dependency on the daf-16/FoxO signaling pathway. These results underscored the effectiveness of ARE as a natural agent for enhancing longevity and stress resilience to C. elegans, potentially to human.